Luaskan Cakrawala, Buka Hati, Buka Mata, Buka Telinga: (Kajian Misiologi Pelayanan Nabi Yunus dan Implikasinya bagi Praktek Penginjilan Masa Kini) - Adolf Antjura (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2021)
When a person is in the midst of his own group and community, it is a natural thing and considered a normal thing if he defends his community or his own group, but if observed and investigated a somewhat excessive sentimentality for the movement in cross-cultural service. An example in this article presents the story of a prophet Jonah who was called and sent by God, to the city of Nineveh, the land of Assyria. Jonah maintains his sense of nationalism, so that he is not willing to be sent by God even though he has responded to God's call, he prefers that the inhabitants of the city of Nineveh be punished by God for their sins, because Jonah thinks that Nineveh is a threat to the Israelites, he does not want the people of Nineveh to repent, to receive God's forgiveness. This article invites us like the prophet Yunus, all of God's people need to open their hearts, open their eyes and open their ears to broaden their views so that they can understand correctly that God also loves other nations or groups, communities. God's people as believers are obliged to have love and care to convey the good news of salvation to all who believe. Abstrak Indonesia Ketika seseorang berada ditengah-tengah kelompok dan komunitasnya sendiri, adalah merupakan sutu kewajaran dan dianggap suatu hal yang normal jika ia membela komunitasnya atau kelompoknya sendiri, namun jika diamati dan diselidiki suatu sentimental yang agak berlebihan bagi pergerakan dalam pelayanan lintas budaya. Suatu contoh dalam artikel ini menampilkan kisah seorang nabi Yunus yang dipangil dan diutus Allah, ke kota Niniwe, negeri Asyur. Yunus mempertahankan rasa nasionalimenya, sehingga ia tidak bersedia diutus Tuhan walaupun ia telah meresponi panggilan Allah, ia lebih memilih supaya penduduk kota Niniwe dihukum Allah atas dosa mereka, karena Yunus beranggapan bahwa Niniwe adalah ancaman bagi bangsa Israel, ia tdak menginginkan penduduk Niniwe bertobat, untuk menerima pengampunan Allah. Artikel ini mengajak kita sebagaimana halnya nabi Yunus, semua umat Tuhan perlu membuka hati, membuka mata dan membuka telingah untuk meluaskan pandangan sehingga dapat memahami dengan benar bahwa Allah juga mengasihi bangsa atau kelompok, komunitas lain. Umat Tuhan sebagai orang yang percaya wajib memiliki kasih dan kepedulian untuk menyampaikan kabar baik yaitu keselamatan kepada semua orang yang percaya.